2006
DOI: 10.1001/archpsyc.63.12.1396
|View full text |Cite
|
Sign up to set email alerts
|

Catechol O-methyltransferase Val158Met Genotype and Neural Mechanisms Related to Affective Arousal and Regulation

Abstract: Our results indicate that heritable variation in dopamine neurotransmission associated with the met allele of the COMT polymorphism results in heightened reactivity and connectivity in corticolimbic circuits. This may reflect a genetic predisposition for inflexible processing of affective stimuli, a mechanism possibly accounting for aspects of arousal and behavioral control that contribute to emotional dysregulation previously reported in met/met individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
284
6
10

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(337 citation statements)
references
References 93 publications
37
284
6
10
Order By: Relevance
“…64 It is noteworthy that the personality domains affected by MAOA genetic variation (Harm Avoidance, Reward Dependence) correspond, in the Cloninger hypothesis, 5 to those neurotransmitter systems (serotonin, norepinephrine) impacted by MAOA during neurodevelopment. 16 In addition, genetic variation in COMT, previously linked to functional coupling in another neural circuit and associated with TPQ Novelty Seeking, 65 was not linked to functional coupling in the circuit identified here. Taken together, these findings are consistent with Cloninger's predictions regarding the neurochemical underpinnings of TPQ traits: Harm Avoidance (serotonin), Novelty Seeking (dopamine) and Reward Dependence (norepinephrine).…”
Section: Discussionmentioning
confidence: 52%
“…64 It is noteworthy that the personality domains affected by MAOA genetic variation (Harm Avoidance, Reward Dependence) correspond, in the Cloninger hypothesis, 5 to those neurotransmitter systems (serotonin, norepinephrine) impacted by MAOA during neurodevelopment. 16 In addition, genetic variation in COMT, previously linked to functional coupling in another neural circuit and associated with TPQ Novelty Seeking, 65 was not linked to functional coupling in the circuit identified here. Taken together, these findings are consistent with Cloninger's predictions regarding the neurochemical underpinnings of TPQ traits: Harm Avoidance (serotonin), Novelty Seeking (dopamine) and Reward Dependence (norepinephrine).…”
Section: Discussionmentioning
confidence: 52%
“…However, a putative effect of tolcapone on noradrenergic and/or dopaminergic neurotransmission within brainstem circuits mediating the startle reflex cannot easily explain the selective startle increase by the drug in the Met/Met group only. Startle reflex increases during negative mood (see Lang and Davis, 2006 for review), and Met homozygotes have reduced resilience against such negative mood states (Smolka et al, 2005;Drabant et al, 2006;Weiss et al, 2007). It is therefore possible that the startle increase by tolcapone in the Met/Met group is related to tolcapone-induced dysphoric mood in Met158 homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Following the landmark study of Egan et al (2001), a range of studies have shown that the Val 158 Met allele has a small but significant impact on prefrontal cognitive performance and efficiency, with Met 158 -carrying individuals performing better and/or more efficiently than Val 158 -carrying individuals (Barnett et al, 2007b). Conversely, the Val 158 allele is associated with more 'flexible' cognitive responses (Bilder et al, 2004), especially during emotional processing (Smolka et al, 2005;Drabant et al, 2006). Apart from Val 158 Met, other common COMT SNPs are noncoding (synonymous, intronic, or in the promoter or 3 0 -untranslated regions).…”
Section: Catechol-o-methyltransferasementioning
confidence: 99%